If the Ley 115 Is "Constructivist" What Does That Imply for the English Curriculum? Neo-Vygotskyan Perspective - William D. Cousin (Asociación Colombiana de Profesores de Ingles, 2016)
The concept of "Constructivism" is often mentioned in connection with the recent educational legislation in Colombia. The historical development is traced to emphasize the idea of negotiating social outcomes which lends itsefl to group work. Examples of the way in which groups can function to foster such social construction are examined. Language teachers have to make room for such socio-cultural negotiations in their classroom and a suggestion for some role plays designed to facilitate such work is presented.